Blood dendritic cells in chronically HIV-1 infected individuals in South Africa: Phenotype, function and immune modulation - De Swardt, Dalene (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016